Time, engagement and video games: How game design elements shape the temporalities of play in massively multiplayer online role‐playing games. (10th February 2021) - Rapp, Amon
Abstract: Researchers and developers constantly seek novel ways to create engaging applications that are able to retain their users over the long term, make them desire to spend time using the application or go back to using it after a break. With this aim, video games can be an insightful source of inspiration, as they are specifically designed to maximise playing time, increase players' intentions of playing during the day or enhance their willingness to replay. In a gaming context, 'time' is an important factor for engagement because game designers can design the game time to retain players in the game environment. Drawing on social practice theory, which is increasingly used in Information Systems (IS) research, I conducted an ethnographic study in World of Warcraft (WoW) to understand how various temporalities are produced within a video game and the effects that they have on players' engagement. The findings show that game temporalities stem from the complex interaction between the design features of the game and the norms, routines and expectations that are part of the game practices. Moreover, these temporalities can engender temporal experiences that may stimulate engagement in various ways. The study contributes to IS literature by proposing a novel understanding of how time can be intentionally designed to sustain user engagement. Finally, it suggests that 'time design' in video games could inspire designs in broader IS contexts, such as in the gamification of online communities, crowdsourcing platforms and crowd working systems.